2022
DOI: 10.1055/a-1783-7718
|View full text |Cite
|
Sign up to set email alerts
|

Blood Pressure Levels and Maternal Outcome in Women with Preeclampsia – a Retrospective Study from a Large Tertiary Obstetric Centre

Abstract: Introduction Patients with high blood pressure levels are at high risk for acute complications as well as serious long-term consequences. Women with preeclampsia often experience very high blood pressure levels during pregnancy and postpartum and are also known to have a higher cardiovascular risk in later life. Material and Methods In our single-centre retrospective cohort study, we analysed 158 pregnancies complicated by preeclampsia in regard to maternal outcome. We divided the patient c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 26 publications
(29 reference statements)
0
6
0
Order By: Relevance
“…In a previous study, we showed that patients with preeclampsia and very high blood pressure during pregnancy developed HELLP syndrome significantly more often than patients with lower blood pressure levels [12]. Therefore, strict blood pressure control might be a possible preventative option to delay or even avoid the severe complications of preeclampsia and related disorders such as HELLP syndrome.…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations
“…In a previous study, we showed that patients with preeclampsia and very high blood pressure during pregnancy developed HELLP syndrome significantly more often than patients with lower blood pressure levels [12]. Therefore, strict blood pressure control might be a possible preventative option to delay or even avoid the severe complications of preeclampsia and related disorders such as HELLP syndrome.…”
Section: Discussionmentioning
confidence: 95%
“…According to previous studies on maternal outcomes with preeclampsia and based on the current international guidelines on arterial hypertension, we divided the patients into three groups according to their maximum prepartum blood pressure 12 13 14 :…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…This led us to the question whether a classification of preeclampsia into different degrees of severity according to maternal blood pressure levels could be helpful for perinatal risk stratification. In a previous study, it could be shown that the level of hypertension in preeclamptic women is an independent marker for maternal outcome [ 12 ]. It remains uncertain if there is a direct impact on the mode of delivery and neonatal outcome.…”
Section: Introductionmentioning
confidence: 99%